LITERASI MEMBACA PERSPEKTIF AL-QUR’AN DAN PRAKTEKNYA DALAM PENDIDIKAN JENJANG MADRASAH TSANAWIYAH (MTs) - Suflawiyah Suflawiyah (STIT AL-AMIN KREO TANGERANG, 2022)
The weak literacy culture of students in Indonesia, based on data on the literacy skills of students in Indonesia, 46,83% fall into the poor category. The development and information of the 21st century or the industrial era 4.0 of education so that students can communicate, think critically, can use technology to solve problems and overcome and face revolutions that require increased creativity and critical reasoning students tend to experience a decline and meanwhile literacy activities only write aspects of reading and less touching activities. Some of the objectives of this research are to find a reading literacy model from the Al-Quran perspective and describe the practice of reading literacy at the Madrasah Tsanawiyah (MTs) level. The method used in this research is descriptive qualitative with the data sources of books, documents and other literature related to the research. The literacy model in the Qur'an, sometimes by writing, reading and understanding God's messages in depth. This model has been proven to give birth to a generation of intellectuals and high integrity. Reading literacy at the madrasah tsanawiyah (MTs) level has literacy activities as an effort to form the actualization of willingness to symptoms of internalization of knowledge and responses.